Using Neural Data to Test a Theory of Investor Behavior: An Application to Realization Utility. (April 2014) - FRYDMAN, CARY; BARBERIS, NICHOLAS; CAMERER, COLIN; BOSSAERTS, PETER; RANGEL, ANTONIO
ABSTRACT We conduct a study in which subjects trade stocks in an experimental market while we measure their brain activity using functional magnetic resonance imaging. All of the subjects trade in a suboptimal way. We use the neural data to test a "realization utility" explanation for their behavior. We find that activity in two areas of the brain that are important for economic decision‐making exhibit activity consistent with the predictions of realization utility. These results provide support for the realization utility model. More generally, they demonstrate that neural data can be helpful in testing models of investor behavior.